Aminophosphine-based continuous liquid-phase synthesis of InP and InP/ZnS quantum dots in a customized tubular flow reactor. Issue 2 (3rd January 2023) - Wang, Zhuang; Segets, Doris
Abstract : Continuous flow synthesis of InP QDs and InP/ZnS core/shell QDs using a premixed precursor solution and a customized tubular flow reactor setup. Abstract : We present a new platform with a customized flow reactor for the continuous synthesis of InP-based quantum dots (QDs) using greener aminophosphine as phosphorus precursor instead of tris(trimethylsilyl)phosphine. With the benefit of a compact reactor configuration (approx. 30 × 25 × 25 cm 3 ) and a premixed precursor solution, InP QDs were successfully synthesized with tunable sizes from 2.7 nm to 3.4 nm and narrow particle size distribution (PSD) with relative standard deviation (RSD) down to 7.7%. In addition, as a proof of principle, InP/ZnS core/shell QDs were also successfully synthesized. Without optimization of the synthesis protocol, a photoluminescence quantum yield (PLQY) of 30.9% was achieved.